Medicinal plants with anti-SARS-CoV activity repurposing for treatment of COVID-19 infection: A systematic review and meta-analysis - EBENEZER, OLUWAKEMI; BODEDE, OLUSOLA; AWOLADE, PAUL; JORDAAN, MARYAM A.; OGUNSAKIN, ROPO E.; SHAPI, MICHAEL (Acta pharmaceutica (Zagreb, Croatia), 2022)
The novel SARS-CoV-2 (severe acute respiratory syndrome coronavirus) has emerged as a significant threat to public health with startling drawbacks in all sectors globally. This study investigates the practicality of some medicinal plants for SARS-CoV-2 therapy using a systematic review and meta-analysis of their reported SARS-CoV-1 inhibitory potencies. Relevant data were systematically gathered from three databases, , Web of Science, PubMed and Scopus. The information obtained included botanical information, extraction method and extracts concentrations, as well as the proposed mechanisms. Fourteen articles describing 30 different plants met our eligibility criteria. Random effects model and subgroup analysis were applied to investigate heterogeneity. According to subgroup analysis, the substantial heterogeneity of the estimated mean based on the values reporting the most potent anti-SARS-CoV 3C--like protease (3CLpro) inhibitors (10.07 %, < 0.0001), was significantly higher compared to the most active anti-SARS-CoV papain-like protease (PLpro) inhibitors (6.12 %, < 0.0001). More importantly, the literature analysis revealed that fruit extracts of L. and the compound cryptotanshinone isolated from the root of ( = 0.8 ± 0.2 μmol L ) were excellent candidates for anti--SARS-CoV targeting PLpro. Meanwhile, iguesterin ( = 2.6 ± 0.6 μmol L ) isolated from the bark of emerged as the most excellent candidate for anti-SARS--CoV targeting 3CLpro. The present systematic review and meta-analysis provide valuable and comprehensive information about potential medicinal plants for SARS-CoV-2 inhibition. The chemotypes identified herein can be adopted as a starting point for developing new drugs to contain the novel virus.